PASTORAL COUNSELING FOR SERVANTS OF GOD FAMILIES IN MANADO WHO EXPERIENCING EMOTIONAL DIVORCE - Agnes BJ Raintung; Daniel Susanto; Novita P Sianturi (Institut Agama Kristen Negeri Manado, 2024)
The family is an institution that cannot be separated from problems. The problems faced by the family can lead the family to an emotional divorce. This emotional divorce is a much more severe condition than a physical or legal divorce. This condition is even more severe if it occurs in a family of God’s servants, because they bear a double burden related to their status. For this reason, it is necessary to think about pastoral counselling for family who experience emotional divorce. This research was conducted using a qualitative method through a case study approach. It is hoped that the findings in this study can provide an understanding of family pastoral counselling for those who experience emotional divorce so that the impact of emotional divorce on family members can be minimized.